A full order sliding mode tracking controller for direct drive robot manipulators - Ahmad, Mohamad Noh; Osman, Johari Halim Shah (IEEE, 2004)
This paper presents the development of a full order sliding mode controller for tracking problem of direct drive robot manipulators. By treating the arm as an uncertain system represented by its nominal and bounded parametric uncertainties, a new robust full-order sliding mode tracking controller is derived such that the actual trajectory tracks the desired trajectory as closely as possible despite the non-linearities and input couplings present in the system. A proportional-integral sliding surface is chosen to ensure the stability of overall dynamics during the entire period i.e. the reaching phase and the sliding phase. Application to a three DOF direct drive robot manipulator is considered.